Analysis and design of multi-storey composite building - Tin, Nann; Tin , Tin Win (2008)
Many types of multistory buildings are the symbols of modernized and developed nations. These buildings are the solution to the problem of living because of population growth. High-rise steel frame and concrete frame structures have been constructed in design of tall buildings in our country as a standard role. But, composite tall building is not situated up to now. Therefore, it is necessary to study special attention in designing the composite tall building. This study deals with composite action in structural members of 5 stories composite building. It belongs to seismic zone 2A. The spans of the sample model are arranged from 10 feet to 30 feet. Analysis of building is carried out by using ETABS Software. In designing beam members, ETABS Software is also used, but CSICOL Software is introduced for column design. Only square sections are used in column design for the purpose of easy to construct the building. The structure is composed of special moment resisting frame by using steel and concrete materials. Seismic load follows the Uniform Building Code (UBC) procedure of equivalent static and dynamic analysis load assumptions and load combinations are also according to UBC provision. In dynamic analysis, response spectrum method is used. Wide flange W-sections are used for frame members associated with reinforced concrete. Floor slabs are designed as metal steel deck supporting concrete slab system. Joints are considered as rigid joints and connection is designed with bolts and weld. Necessary checking is carried out for the stability of the superstructure.